Implementation of Health Law at a Remote Community Health Center in Indonesia: Challenges and Strategies - Priyanto, Priyanto; Satrio, Andri Putro; Asep Sapsudin (Research Horizon, 2025)
Community health centers serve as the frontline of primary health care in Indonesia, yet their ability to deliver quality services in remote areas is often limited by gaps between legal mandates and daily practice. This study examines the implementation of health law at Health Center, and identifies practical strategies to improve service quality and legal compliance. The research combined juridical-normative analysis of relevant national laws and regulations with empirical data collected through observation, in-depth interviews with the head of the health center, staff, and patients, and document review at the health center. Thematic analysis was applied to assess alignment between legal standards and actual practice. Findings reveal that the health center consistently applies standard operating procedures, maintains active promotive-preventive-curative-rehabilitative programs, and provides accessible complaint mechanisms. However, persistent personnel shortages, inadequate infrastructure, and low legal awareness among staff and community members continue to hinder full compliance with minimum service standards. Management responds through regular internal training, gradual infrastructure improvement using operational funds, and cross-sectoral collaboration with local leaders and village cadres. These efforts demonstrate that service quality in remote areas can be strengthened through continuous capacity building and community involvement.